The complete mitochondrial genome sequence of Dodona eugenes (Lepidoptera: Riodinidae) - Wei, Zhong-Xue (Mitochondrial DNA B Resour, 2021)
The complete mitochondrial genome (mitogenome) sequence of Dodona eugenes (Lepidoptera: Riodinidae) was determined and analyzed. The mitogenome is 15,680 bp in length with consisting of 13 protein-coding genes (PCGs), 22 transfer RNA (tRNA) genes, two ribosomal RNA genes (rrnL and rrnS), and one AT-rich region. The gene content, orientation, and order are identical to that of the majority of other lepidopteran insects. The D. eugenes mitogenome includes a cox1 gene with an atypical CGA(R) start codon and three genes (cox1, nad5, and nad4) exhibiting incomplete stop codons. All tRNAs have a typical secondary cloverleaf structure, except for trnS1 which lacks the dihydrouridine (DHU) arm. The 825-bp long AT-rich region is the longest among sequenced riodinids, which range from 349 to 423 bp. The conclusion of phylogenetic analysis highly supported the monophyly of Riodinidae, which is standing as the sister of the family Lycaenidae.